Multiple Intelligences (MI) on Developing Speaking Skills - Shelawati Rizqiningsih; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2019)
The current study investigates the impact of multiple intelligences-based Instructions on developing speaking skills of the students of English. Therefore, the problem of the current study can be stated in the lack of speaking skills of the students of English school in Junior High School, MTs Al-Ihsan Jakarta Barat. To confront this problem, the researcher developed a multiple intelligences-based program to enhance the speaking skills paying due attention to the individual differences among students. The sample of the study consisted of sixty fourth-year perspective students of English. The Quasi-experimental research design was used in the study as the researcher used the one group post-test to assess the usefulness of using this approach. Results of the study proved the effectiveness of Multiple Intelligences-(MI) On Developing Speaking Skills of the 9th Grade Students’ of MTs Al-Ihsan Jakarta Barat.